The co-infection with Ehrlichia minasensis, Anaplasma marginale and Anaplasma platys is not associated with anemia in beef cattle in the Brazilian Pantanal - André, Marcos Rogério [UNESP]; Calchi, Ana Cláudia [UNESP]; Herrera, Heitor Miraglia; Zanatto, Diego Carlos de Souza [UNESP]; Horta, Bruna de Carvalho Le Senéchal [UNESP]; Tasso, Júlia Banhareli [UNESP]; de Souza Ramos, Inalda Angélica [UNESP]; de Mello, Victória Valente Califre [UNESP]; Machado, Rosangela Zacarias [UNESP] (Elsevier, 2020)
The Anaplasmataceae family is composed of obligatory intracellular Gram-negative bacteria transmitted by arthropod vectors. In Brazil, with the exception of Anaplasma marginale, little is known about the occurrence of other Anaplasma and Ehrlichia species infecting cattle. The present study aimed at investigating the occurrence of Anaplasma spp. and Ehrlichia spp. in beef cattle (Bos indicus) sampled in the Brazilian Pantanal, an area prone to periodic flooding and endemic for bovine trypanosomiasis. Blood samples from 400 cattle were collected and screened by PCR assays based on rrs and dsb genes from Anaplasma spp. and Ehrlichia spp., respectively. Positive samples for Anaplasma spp. were subjected to qPCR assays based on the msp-2 gene and nPCR based on the groEL gene. As a result, 4.75% (19/400) and 48.12% (167/347) were positive for Anaplasma platys and Ehrlichia minasensis, respectively. Besides, positivity of 56.75% (227/400) for A. marginale and seropositivity of 90.75% (363/400) for Trypanosoma vivax were found. A high rate of co-infection was observed (67.25%), from which the co-infection by A. marginale and E. minasensis was more frequently found in calves than cows. Interestingly, none of the animals presenting co-infection showed anemia or other clinical signs. The present study showed, for the first time, the occurrence of A. platys and E. minasensis in beef cattle in the southern Pantanal, as well as a high rate of co-infection by A. marginale, E. minasensis and T. vivax in the sampled animals.
Keywords: Anaplasma marginale; Anaplasma platys; Anaplasmataceae; Bovine anaplasmosis; Ehrlichia minasensis